PERBANDINGAN PENGGUNAAN KONDENSOR BERPENDINGIN UDARA DENGAN KONDENSOR BERPENDINGIN AIR PADA LEMARI PENDINGIN - Korawan, Agus Dwi (Jurnal Rekayasa Mesin, 2024)
Refrigerators are one of the common machines for Indonesian people. Refrigerators can be used to store foods and ingredients for longer shelf life. The temperature in the refrigerator and freezer is low because the heat is absorbed by the evaporator and then released into ambient air through the condenser. The heat transfer velocity from the condenser to ambient air depends on the convection heat transfer coefficient of air. This study was conducted experimentally by comparing the refrigerator's performance that use air-cooled condensers and water-cooled condensers. The equipment used is a refrigerator with a portable water bath. This study aims to know the temperature change speed in the storage room and freezer room, the temperature changes before and after the condenser was used, and the change of the temperature and pressure in refrigerant before and after the evaporator was used. The results showed refrigerator with a water-cooled condenser can give cooling process in the storage room faster, give freezing process in the freezer room faster, and enhance COP.